Implementation of Pssr As a Constituent of PSM to Enhance Occupational Safety - Sainyakit, Rofina; Nugroho, Budi Sulistiyo; Sriana, Tun; Adhytama, Vidya Putra (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2024)
High-risk process industries involve the management of hazardous substances, which can lead to safety incidents if not appropriately managed. This research aims to assess the impact of the Pre-Startup Safety Review (PSSR) on improving occupational safety at PT X as a component of the Process Safety Management (PSM) framework. The approach was descriptive qualitative, using a case study method that included internal document review and interviews with relevant stakeholders. The findings revealed that while most critical equipment had been inspected and confirmed as operationally ready, operational issues were previously overlooked, such as leaks in the BFW line and failures in the NG PCV, which resulted in delays in the process. This highlights the need for a more thorough review of the PSSR checklist to ensure all potential issues are identified in advance. In summary, the effectiveness of PSSR at PT X can be improved through increased monitoring and follow-up of any problems identified during the start-up phase.